Good Practices and Trends in Reverse Logistics in the plastic products manufacturing industry - Félix, M.J. (2020)
The management of solid waste and its impact on the environment has been a subject of study and revision in different aspects, from mathematical modeling to control, with the aim of proposing different alternatives that contribute to diminishing the adverse effects in the environment. In this regard, reverse logistics has become a key trend to balance economic development with environmental protection, as this approach allows the maximization of value and the sustainable use of products at the end of their life cycle. This approach has been applied in different sectors such as textiles, pharmaceuticals, food, among others, but still with great potential for study in the plastic industry given the impact of plastic products on the environment and the increasing pressures of consumers, government and environmental groups that propose new forms of operation and innovation in companies in the sector. The goal of this work is the identification of good practices and trends in the plastic products manufacturing industry, with respect to the recovery of plastic products through reverse logistics, both at the revision level of literature, as well as, from the use of an evaluation instrument among entrepreneurs of the sector, in order to provide a framework for diagnosis and continuous improvement in the development of good practices in reverse logistics for the industry.